2010
DOI: 10.4209/aaqr.2010.07.0059
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Source Apportionment of Atmospheric Carbonyl Compounds in Urban Kaohsiung, Taiwan

Abstract: The concentrations of 18 atmospheric carbonyls species were measured at Nan-Chie and Hsiung-Kong sites in Kaohsiung City, Taiwan, during the summer and winter of 2006. Formaldehyde and acetaldehyde were the most abundant carbonyls with respective annual mean concentrations of 17.99 μg/m 3 and 13.69 μg/m 3 at Nan-Chie, and 21.47 μg/m 3 and 16.68 μg/m 3 at Hsiung-Kong; altogether the two species accounted for approximately 56-57% of total carbonyls. In summer, the total concentrations of carbonyls were 74.06 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…The air quality in Kaohsiung City is the worst in Taiwan due to emissions from these industrial complexes and traffic. Moreover, the unfavorable meteorological conditions (e.g., poor atmospheric mixing, declining visibility, and the sealand breeze circulation) also have a significant impact on the air quality (Wang et al, 2010). Although several studies have reported the spatial distribution and source apportionment of PAHs in urban areas, industrial areas, and sediments in Taiwan (Fang et al, 2004;Yang and Chen, 2004;Chen et al, 2009;Chen et al, 2012), those of atmospheric PAHs from petrochemical industrial complexes have not yet been adequately characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The air quality in Kaohsiung City is the worst in Taiwan due to emissions from these industrial complexes and traffic. Moreover, the unfavorable meteorological conditions (e.g., poor atmospheric mixing, declining visibility, and the sealand breeze circulation) also have a significant impact on the air quality (Wang et al, 2010). Although several studies have reported the spatial distribution and source apportionment of PAHs in urban areas, industrial areas, and sediments in Taiwan (Fang et al, 2004;Yang and Chen, 2004;Chen et al, 2009;Chen et al, 2012), those of atmospheric PAHs from petrochemical industrial complexes have not yet been adequately characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde is also a by-product from cigarette smoking and fuel-burning (Daisey et al, 1994;Crump et al, 1997;Hodgson et al, 2000;Hippelein, 2004;Bari et al, 2011). Despite, high concentration levels of formaldehyde are also found in outdoor urban environment (Wang et al, 2010). Using heterogeneous PCO for the degradation of formaldehyde has been considered as a promising technique.…”
Section: Introductionmentioning
confidence: 99%
“…The application of principal components analysis (PCA) manner to data sets produces statistically independent linear combinations of original variables, and also explains most of the total variation with reduced dimensions. This method has been successfully applied to identify potential sources of air pollutants and analyse relationships between distinct air pollutants in measured data (Horel, 1981;Yu et al, 2000;Shi et al, 2009;Abhishek et al, 2010;Wang et al, 2010;Kothai et al, 2011;Amodio et al, 2013;Liang et al, 2013). Some research studies have been conducted with the aim of predicting the ozone generation based on the meteorological conditions and the pollutants-precursor appearing at a particular point in time (Abdul-Wahab et al, 2002.…”
Section: Introductionmentioning
confidence: 99%